The psychometric properties of the Arabic version of the Teachers’ Attitudes towards Differentiated Instructional Scale - Alnahdi, G. H.; Pozas, Marcela; Sulaimani, Mona F.; Letzel-Alt, V. (Frontiers in Psychology, 2025)
According to literature, teachers’ attitudes are a strong predictor of their differentiated instructional practice. However, empirical research exploring teachers’ attitudes, specifically towards the practice of DI, is still quite limited. Currently, there is only one instrument available that assesses teachers’ attitudes towards DI, that is the Teachers’ Attitudes towards Differentiated Instructional Scale (TAT-DIS), which has not been explored within any Arabian country. With this background, this study examines the psychometric characteristics of the Arabic version of the tool. A total 221 teachers in two Arabic countries, Egypt and Saudi Arabia, participated in the study. Results of the confirmatory analysis confirmed the hypothesized two-factor structure and internal consistencies of the subscales were good. Limitations and implications of the study are further discussed.